An spike-accum® bioconjugate protein vaccine confers potent SARS-CoV-2-specific immunity - Jean Pierre Bikorimana; Nathanael A. Caveney; Nehme EL-Hachem; Gabrielle A. Mandl; John A. Capobianco; Daniela Stanga; Jamilah Abusarah; Mark A. Hancock; Roudy Farah; Marina P. Gonçalves; Darryl Falzarano; Mingmin Liao; et al. (iScience)
Summary: Despite the recent control of COVID-19, the devastating effects caused by the 3-year pandemic highlight the importance of developing effective vaccines to rapidly address future outbreaks. The present study describes a novel Spike (Sp) protein-based vaccine formulation using the Accum® platform. Although Sp-Accum® bioconjugation does not alter the overall protein structure, it triggers a substantial antibody titer: i) exhibiting higher specificity toward the S1 domain of Sp, ii) neutralizing Sp-ACE2 interactions, and iii) cross-reacting with various Sp variants. Besides validating the vaccine immunogenicity in rabbits, its administration in a “gold-standard” SARS-CoV-2 hamster model was shown to be safe while accelerating viral clearance without eliciting signs of pathological inflammation in the lungs of infected animals. Altogether, this proof-of-concept study not only demonstrates once again the versatility of the Accum® technology in vaccine engineering, but it provides an enabling technology for the rapid development of value-added, protein-based vaccines for future pandemics.